COMPARATIVE EFFECTIVENESS OF CEFTRIAXONE IN COMBINATION WITH MACROLIDE VERSUS CEFTRIAXONE ALONE FOR PAEDIATRIC PATIENTS HOSPITALIZED WITH COMMUNITY-ACQUIRED PNEUMONIA - Dr Amjad Mustafa; Dr Shazia Sarwat Iqbal; Dr Shafiq Ahmad; Dr Rahman Shah; Muhammad Shahid; Dr Tahira Jehangir (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Mycoplasma pneumoniae infection should be taken seriously when treating pneumonia contracted in the community. Empirical therapy using beta-lactam and macrolide antibiotics is advised. There is, however, little data to back up this suggestion. The purpose of this research is to compare the advantages of ceftriaxone individually vs ceftriaxone with macrolide with respect to hospitalization duration.Methods: We used Poisson regression and propensity-score analyses to evaluate the relationship between antibiotic therapy and the duration of stay in a retrospective cohort analysis of 1200 kids who had pneumonia, aged 1 to 16 years. Furthermore, log-treatment costs were assessed using multivariable linear regression and propensity-score analyses, which adjusted for the initial assessments and treatments, hospitals and patient details, and other factors.Results: In a 2023 study at Lady Reading Hospital involving 1200 children aged 1-16 years with pneumonia, most were treated with either ceftriaxone alone or ceftriaxone plus a macrolide, with one-third receiving combination therapy more commonly among school-aged children. The study found that combination therapy recipients were generally older and had fewer hospitalizations during respiratory seasons. Among 560 analyzed children, over 40% had both pneumonia and asthma. Those on combination therapy were more likely to receive additional treatments like steroids and beta-agonists. Both groups had similar lengths of stay, with a median of 2.5 days and a mean of 3.1 days. Preschoolers on combination therapy had 25% higher hospital costs, though no significant difference in length of stay, while school-aged children had a 10% shorter length of stay but higher costs. There were no significant differences in readmission rates, inpatient deaths, or critical care transfers.Conclusions: Children of preschool age were unlikely to gain anything from the combination therapy, and it was more expensive. The combination of therapies was associated with a shorter hospital stay for kids of school age without having a discernible financial impact. The creation of accurate point-of-care diagnostic tools to detect M. pneumoniae infections among kids may facilitate prescribing of targeted macrolides and the execution of comparable efficacy research on designed combination treatments.